The immediate effect of a single session of pain neuroscience education on pain and the autonomic nervous system in subjects with persistent pain, a pilot study - Sillevis, Rob; Trincado, Gabriel; Shamus, Eric (PeerJ, 2021)
Background The autonomic nervous system is a system that operates at the subconscious level and has been associated with neurobehavioral aspects of pain. Overall, persistent pain has a stimulating effect on the sympathetic nervous system. A promising emerging nonpharmacological treatment to manage persistent pain is neuroscience-based pain education. The overarching goal of neuroscience-based pain education is to change cognitions about pain and the pain experience through education. The aim was to determine the immediate and short-term impact of a neuroscience-based pain education video on the autonomic nervous system and pain in a subgroup of individuals with persistent pain. Methods A convenience sample of 26 subjects were recruited for this study. Each subject indicated their pain level at the time of testing using a Visual Analogue Scale. Automated pupillometry was utilized to measure pupil diameter. After two minutes of accommodation to the goggles, the pupil was measured continuously for 60 s. Following this a 5-minute video presentation “Understanding Pain” was watched, followed by a continuous pupil measurement for 60 s. Three minutes after this measure, the final pupil diameter measurement was taken for 60 s. After completing the final pupil measure, the subject was asked to fill out a second Visual Analogue Scale and a Global Rate of Change. Outcomes Each subject completed a Global Rating of Change Scale and the mean score was 1.14 (SD = 1.61 and a SEM = 0.), supporting the hypothesis of an overall self-perceived benefit from the intervention. There was a statistically significant difference in pain following the video, P < 0.01. A significant correlation was observed between the self-perceived decrease in pain level and the Global Rating of Change score, p = 0.02. There was no statistically significant difference in the mean pupil diameter following the video with p = 0.76 for the right eye and p = 0.250 for the left eye. Discussion This pilot study demonstrated that a 5-minute neuroscience-based pain education video reduced perceived pain in a small sample of subjects with persistent pain. Watching the neuroscience-based pain education video did not seem to result in an immediate generalized autonomic nervous system response. However, it resulted in a different reaction on each eye. This unequal response might be the result of the hemispheric lateralization of the ANS. This study supports the fact that the pain experience is determined by the balance between conscious cognitive processes and subconscious processes based on previous psychological experiences.
Keywords: Neuro pain science education; Autonomic nervous system; Pupillometry; Chronic pain